SPEAR: The Next Generation GFDL Modeling System for Seasonal to Multidecadal Prediction and Projection. (11th March 2020) - Delworth, Thomas L.; Cooke, William F.; Adcroft, Alistair; Bushuk, Mitchell; Chen, Jan‐Huey; Dunne, Krista A.; Ginoux, Paul; Gudgel, Richard; Hallberg, Robert W.; Harris, Lucas; Harrison, Matthew J.; Johnson, Nathaniel; et al.
Abstract: We document the development and simulation characteristics of the next generation modeling system for seasonal to decadal prediction and projection at the Geophysical Fluid Dynamics Laboratory (GFDL). SPEAR (S eamless System for P rediction and EA rth System R esearch) is built from component models recently developed at GFDL—the AM4 atmosphere model, MOM6 ocean code, LM4 land model, and SIS2 sea ice model. The SPEAR models are specifically designed with attributes needed for a prediction model for seasonal to decadal time scales, including the ability to run large ensembles of simulations with available computational resources. For computational speed SPEAR uses a coarse ocean resolution of approximately 1.0° (with tropical refinement). SPEAR can use differing atmospheric horizontal resolutions ranging from 1° to 0.25°. The higher atmospheric resolution facilitates improved simulation of regional climate and extremes. SPEAR is built from the same components as the GFDL CM4 and ESM4 models but with design choices geared toward seasonal to multidecadal physical climate prediction and projection. We document simulation characteristics for the time mean climate, aspects of internal variability, and the response to both idealized and realistic radiative forcing change. We describe in greater detail one focus of the model development process that was motivated by the importance of the Southern Ocean to the global climate system. We present sensitivity tests that document the influence of the Antarctic surface heat budget on Southern Ocean ventilation and deep global ocean circulation. These findings were also useful in the development processes for the GFDL CM4 and ESM4 models. Plain Language Summary: In this paper we describe the development and simulation characteristics of a new climate model that will be used for seasonal to multidecadal climate prediction and projection. The model combines a set of newly developed components that simulate the ocean, atmosphere, land, and sea ice. We document this model by assessing its performance in simulating the current climate and by showing the model's response to changing greenhouse gases and aerosols over the 20th and 21st centuries. We also show results from a set of sensitivity experiments that were an important part of the model development process. These sensitivity tests explore connections between the surface energy balance over Antarctica and the circulation of the deep ocean. Key Points: Development and performance of the next generation GFDL seasonal to decadal prediction model is documented The response of this model to realistic radiative forcing changes is shown via a large ensemble of climate simulations for 1921–2100 The influence of the Antarctic surface energy balance on the world ocean was crucial in model development as shown via sensitivity tests